Il degrado dei materiali lapidei in ambiente sommerso - La Russa, Mauro Francesco; Ricca, Michela (Archeomatica, 2018)
The paper presents an overview of the main causes of decay affecting archaeological stone materials in underwater environments. It is a complex phenomenon so far quite investigated, where a multitude of factors is involved. Degradation forms in seawater imply not only a variation in the physico-mechanical and geochemical properties of materials, but also an aesthetic damage, due to superficial deposits, which can determine to the illegibility of the artefacts. In this context, it is crucial to determine to what extent these decay factors, mainly attributable to biological growth, could affect the durability of materials and what are the effects of new and suitable procedures for their maintenance and protection.